A CASE STUDY OF THE IMPLEMENTATION AND CHALLENGES OF PERSONAL FINANCIAL MANAGEMENT AT THE MUHAMMADIYAH HAJJAH NURIYAH SHABRAN ISLAMIC BOARDING SCHOOL - Risma Fadhilah; Surya Jatmika (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The Muhammadiyah Hajjah Nuriyah Shabran Islamic Boarding School, Muhammadiyah University of Surakarta, is an institution that produces Muhammadiyah cadres at Muhammadiyah University of Surakarta. As students who live in the dormitory, the students of Shabran Islamic Boarding School are faced with the challenge of managing their personal finances independently. The purpose of this study is to determine the implementation of personal financial management, the obstacles experienced, and the supporting factors for the personal financial management of the students of the Muhammadiyah Hajjah Nuriyah Shabran Islamic Boarding School, Muhammadiyah University of Surakarta. This research is a case study with a qualitative approach. Data collection was carried out through interviews and documentation. Data analysis techniques include data collection, data reduction, data presentation, and conclusions. The results of the study show that the personal financial management carried out by the students is in the form of: (1) keeping a simple monthly expenditure record, (2) allocating savings funds of 10-20% of monthly income. Factors that inhibit the personal financial management of students are: (1) still being influenced by the behavior of their friends, (2) lack of support from parents and the Islamic boarding school environment in the management of students' personal finances. Supporting factors in students' personal financial management include self-motivation to manage their finances more systematically, avoid wasteful spending, and conduct self-evaluations to ensure a brighter future. With this research, it is hoped that the Islamic boarding school can encourage more organized personal financial management among all students.